Relationship between the Left Atrial Volume Index and Left Ventricular Geometry and the Incidence of Atrial Fibrillation in Hypertensive Patients with Cardiovascular Complications - Chairatu Sadrina Djeni; Teuku Heriansyah; Mudatsir; Novita; Haris Munirwan (Postgraduate, University of Mataram, 2025)
This study aimed to evaluate the relationships of the left atrial volume index (LAVI) and left ventricular geometry with the incidence of AF in hypertensive patients with cardiovascular complications such as heart failure or coronary arterial disease. This study employed a retrospective observational cohort design. A total of 202 subjects met the inclusion and exclusion criteria for the study. The subjects were selected from hypertensive patients with cardiovascular complications treated at Dr. Zainoel Abidin General Hospital Banda Aceh, a tertiary referral center in Indonesia, between July and December 2024. 12At the end of the study, the participants were divided into two groups: those with newly diagnosed atrial fibrillation (n=37) and those without atrial fibrillation (n=165). The diagnosis of new-onset atrial fibrillation was based on medical records obtained during hospitalization and continued through a three-month follow-up after discharge via outpatient clinic visits and 12-lead ECG monitoring. The study revealed a significant association between increased LAVI and AF incidence (p < 0.01). The mean LAVI in the AF group was 49.9 ± 19.2 ml/m², whereas it was 33.34 ± 15.6 ml/m² in the non-AF group. Additionally, changes in left ventricular geometry were correlated with increased AF incidence (p value = 0.03), with eccentric hypertrophy showing the highest AF incidence (29.5%). A strong association was also found between increased LAVI and left ventricular geometric changes, with eccentric hypertrophy resulting in the highest mean LAVI (43.2 ± 16.9 ml/m²). The odds ratio (OR) analysis demonstrated that patients with LAVI above the threshold had a significantly greater risk of developing AF (OR: 5.2; 95% CI: 2.475–11.161). Similarly, patients with normal ventricular geometry had a significantly lower risk of AF compared to those with eccentric hypertrophy (OR: 0.148; 95% CI: 0.049–0.449). Increased LAVI and left ventricular geometry changes, particularly eccentric hypertrophy, are significant risk factors for AF in hypertensive patients with cardiovascular complications such as heart failure and coronary arterial disease. Clinical practice should incorporate echocardiographic monitoring of left ventricular geometry and LAVI to prevent the progression of AF and detect risk early